PENGARUH LINGKUNGAN KERJA TERHADAP LOYALITAS KARYAWAN DI PANGERAN BEACH HOTEL PADANG - Putri, Aulia Arida (RC-INSTITUT, 2019)
This study aims to determine the effect of the work environment on employee loyalty at Pangeran Beach Hotel Padang. This type of research is classified as associative causal. The population in this study were hotel employees and the number of samples in this study amounted to 106 employees who lived with sampling techniques using probability sampling methods. Data collection techniques were carried out using a questionnaire with a Likert scale that had been tested for validity and reliability. Technical analysis uses the help of the SPSS Computer Program version 16.00. The results showed: (1) The Work Environment was in a very good category (46.22%), (2) Employee Loyalty was in the good category (91.51%) (3) The results of the simple linear regression hypothesis test were obtained F 19,780 with sig . 0,000 <0,05, then the work facility variable can explain the variable of employee satisfaction significantly, with the R Square value of 0,160. This means that work facilities affect the employee's employment by 16% and 84% are influenced by other factors. Based on the results of the research, researchers suggest that more maximizing the work environment in hotels and employees further enhance the work loyalty of Pangeran Beach Hotel Padang.